Effect of Indigofera zollingeriana Top Leaf Meal Supplementation as Natural Antioxidant Source on Production and Quality of Pegagan Duck Eggs - Rizki Palupi; Fitri Novaliya Lubis; Rismawati Rismawati; Iwan Sudibyo; Ramadhan Al Rafi Siddiq (Buletin Peternakan, 2018)
This study aims to produce Pegagan duck eggs which is high in antioxidants to be used as functional comestibles. Efforts to achieve these goals can be done by adding a source of natural antioxidants in the form of legume leaves of Indigofera zollingeriana which contain active compounds of β-carotene. The study used a completely randomized design (CRD) consisting of 5 treatments (4 replications each), which were levels of Indigofera zollingeriana top leaf meal supplementation (R0 = 0%, R2 = 1%, R2 = 2%, R3 = 3% and R4 = 4%) in Pegagan duck rations. The observed variables are production performance; egg quality, both physically and chemically. Physical quality includes egg weight, eggshell percentage, egg white weight percentage (albumen), and weight percentage of egg yolk and egg yolk color. The quality of egg chemistry includes the content of vitamin A, β-carotene, cholesterol, and antioxidant activity of eggs. The data obtained were analyzed by variance analysis, followed by the Duncan Multiple Range Test. The results showed that supplementation of Indigofera zollingeriana top leaf meal in rations could improve egg quality and contain antioxidants. Supplementation of Indigofera zollingeriana top leaf meal with a dose of 4% in rations can increase the color of the yolk by 43.40%, reduce the inhibition rate by 11.38%, with an increase in the content of β-carotene by 75.23% and can maintain normal cholesterol in eggs.